Strategies for Instilling Religious Tolerance Character in Elementary Schools : A Systematic Literature Review - Fatimah, Siti; Safira, Putri Silviana; Mustafsiroh, Vifva Khotul; Romadhona, Istighfara Ayun Tomia; Ismiyah, Binti Rohmiatul; Sofiati, Maulida (Proceeding of International Conference on Islamic Education (ICIED), 2025)
Indonesian is a nation rich in diversity. One of Indonesia’s diversities is religious diversity, which is both an asset and a potential source of conflict if not accompanied by mutual respect. Therefore, a strategy of instilling religious tolerance character from elementary school level is very important to prevent conflict and build character that respect. This study aims to systematically analyze the strategies for instilling religious tolerance in elementary school. This research uses a Systematic Literature Review (SLR) approach, with data sources obtained from Google Scholar, Open Knowledge, Garuda, Crossref, ResearchGate, and Neliti. The research results show that strategies for fostering religious tolerance can be classified into five aspects: teaching methods, subjects, school culture, school programs, and the use of school facilities. This research shows that religious tolerance education in elementary schools can be implemented in many ways, enabling the formation of students' characters that value diversity and fostering a harmonious and peaceful school environment.